2022
DOI: 10.1186/s40795-022-00627-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of undernutrition using the composite index of anthropometric failure (CIAF) and its determinants: A cross-sectional study in the rural area of the Bogor District in Indonesia

Abstract: Background The Composite Index of Anthropometric Failure (CIAF) can comprehensively identify undernutrition by combining several indicators of nutritional status – namely, weight-for-age, length/height-for-age and weight-for-length/height – to determine the nutritional status of children under five years of age. This study aims to assess undernutrition using the CIAF and its determinants on children under five years of age in the Bogor District, Indonesia. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 56 publications
2
19
2
1
Order By: Relevance
“…42 Another similar study involving 330 toddlers in rural areas in West Java Province in Indonesia reported similar results, namely the prevalence of stunting in older toddlers (25-59 months) was higher (37.4%) compared to younger toddlers (0-24 months) that is as much as 17.6%. 16 condensed milk is a significant contributor to malnutrition in children. Therefore, this study also reported that sanitation facilities, water treatment, and clean living behavior are determined by stunting.…”
Section: Stunting and Influencing Factorsmentioning
confidence: 99%
“…42 Another similar study involving 330 toddlers in rural areas in West Java Province in Indonesia reported similar results, namely the prevalence of stunting in older toddlers (25-59 months) was higher (37.4%) compared to younger toddlers (0-24 months) that is as much as 17.6%. 16 condensed milk is a significant contributor to malnutrition in children. Therefore, this study also reported that sanitation facilities, water treatment, and clean living behavior are determined by stunting.…”
Section: Stunting and Influencing Factorsmentioning
confidence: 99%
“…As a secondary outcome of the study, the Composite Index of Anthropometric Failure (CIAF) was used to summarize multiple indicators of child nutritional status. It combines measures of stunting, wasting, and underweight into a single index [22,31]. We further categorized them into seven groups, each representing a speci c combination of nutritional failures, such as no failure, wasted only, stunted only, underweight only, wasted with underweight, stunted with underweight, and stunted, wasted and underweight.…”
Section: Outcome Variablesmentioning
confidence: 99%
“…Other variables included in this study were identi ed through literature searches and determined based on existing evidence from LMICs and Bangladesh [7,8,21,22,24,25,31]. The covariates we included were child's age (continuous), child's sex (male or female), religion (Muslim or non-Muslim), sex of the household head (male or female), education level of the child's mother (no formal education, primary, secondary or higher), education level of the child's father (no formal education, primary, secondary or higher), employment status of the child's mother (unemployed or employed), household size (1-5 members, 6-10 members or 10 + members), place of residence (urban or rural) and administrative divisions (Barishal, Chattogram, Dhaka, Mymensingh, Khulna, Rajshahi, Rangpur or Sylhet).…”
Section: Other Variables/covariatesmentioning
confidence: 99%
“…Accordingly, the odds of developing CIAFs were 75% higher among children living in families that had ve or more family members [AOR = 1.75, 95% CI: Bogor city, Indonesia (42.1%) [9], other areas of India, west Bengal (50.2%) [27], Nagpur (58.6%) [28], Anganwadi (51.8%) [29], rural areas of Bengal (32.7%) [30] and Yemen (70.1%) [31], in Tanzania (38.2%) [11] and Malawi (50.6%) [15].…”
Section: Prevalence Of Composite Indicators Of Anthropometric Failuresmentioning
confidence: 99%
“…Furthermore, according to the study conducted in 34 low and middle-income countries (LMICs) in 2019, about 36% of under-ve children had CIAFs, of which 13.7% had double growth failures (12.0% stunted and underweight, 1.7% wasted and underweight), and 1.5% had triple growth failures [ 8]. Likewise, the prevalence of CIAFs was in Indonesia [9], 62% in India [10], 38.5% in Tanzania [11], and 50.6% in Malawi [12].…”
Section: Introductionmentioning
confidence: 99%